2022
DOI: 10.1038/s41557-022-00949-6
|View full text |Cite
|
Sign up to set email alerts
|

An autonomously oscillating supramolecular self-replicator

Abstract: A key goal of chemistry is to develop synthetic systems that mimic biology, such as selfassembling, self-replicating models of minimal life forms. Oscillations are often observed in complex biological networks, but oscillating, self-replicating species are unknown, and how to

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
50
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(65 citation statements)
references
References 41 publications
0
50
0
Order By: Relevance
“…The ultrasensitive response of the coacervates in our work is attributable to the competition of the reactive radicals between the methacrylate monomer and molecular oxygen. , As described above, molecular oxygen diffused from the air effectively quenches reactive radical species at a lower frequency to generate a threshold, whereas the amount of the radicals produced at a higher frequency becomes higher than that of molecular oxygen to proceed radical polymerization, resulting in the ultrasensitive response. Such an ultrasensitive response based on the competitive mechanism is considered as a new example of light-fueled dissipative systems. , To date, it has been reported that coacervates can provide a microenvironment to accelerate catalytic reactions mainly through molecular sequestration , and to realize stimulus responses towards reactive molecules ( e.g. , assembly–disassembly). ,,,,, Compared with these examples, one of the important aspects of our work is to combine the rate enhancement effect with competitive inhibition via continuous supply of diffusing O 2 , which establishes a unique system in response to temporally distinct stimulus patterns.…”
Section: Resultsmentioning
confidence: 99%
“…The ultrasensitive response of the coacervates in our work is attributable to the competition of the reactive radicals between the methacrylate monomer and molecular oxygen. , As described above, molecular oxygen diffused from the air effectively quenches reactive radical species at a lower frequency to generate a threshold, whereas the amount of the radicals produced at a higher frequency becomes higher than that of molecular oxygen to proceed radical polymerization, resulting in the ultrasensitive response. Such an ultrasensitive response based on the competitive mechanism is considered as a new example of light-fueled dissipative systems. , To date, it has been reported that coacervates can provide a microenvironment to accelerate catalytic reactions mainly through molecular sequestration , and to realize stimulus responses towards reactive molecules ( e.g. , assembly–disassembly). ,,,,, Compared with these examples, one of the important aspects of our work is to combine the rate enhancement effect with competitive inhibition via continuous supply of diffusing O 2 , which establishes a unique system in response to temporally distinct stimulus patterns.…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, limited experimental parameters are involved in tuning the diffusion instead of the complex kinetic matching and harsh reaction selectivity requirements in homogeneous systems. This strategy can be further extended to multi-compartment systems 45,46 and liquidliquid phase separation systems. [47][48][49][50] Passive diffusion and active transport can be developed in controlling the transport of chemical fuels or deactivators between compartments.…”
Section: Discussionmentioning
confidence: 99%
“…Various synthetic analogs achieving structural diversities and functions have been introduced including emulsions, 38 hydrogels, 39 nanoreactors, 40 molecular motors, 41 polymersomes 42 and steady-state supramolecular polymers. 43 Use of diverse types of fuels has created a repertoire of complex biomimetic out-of-equilibrium systems such as enzyme-catalyzed pH cycles for the transient control of polymer fluids 44 and breathing microgel, 45 carbodiimide for self-selection of primitive reaction-network, 46 thiols for self-replicating micelles, 47 and DNA for constructing nanodevices for drug release and reaction networks. 31,[48][49] While these fuels provide a structural component for generating the nonequilibrium phases, utilization of the fuels to perform biomolecular functions in the time domain would further enrich our understanding of systems chemistry and produce effective biomimetic scaffolds including molecular adhesives.…”
Section: Introductionmentioning
confidence: 99%